2018
DOI: 10.1111/eip.12552
|View full text |Cite
|
Sign up to set email alerts
|

Discharges from an early intervention in psychosis service: The effect of patient characteristics on discharge destination

Abstract: Diagnosis and duration of treatment were significant predictors of discharge destination. Patients with diagnoses of enduring psychotic illness, were more likely to be discharged to a secondary psychiatric service irrespective of gender, ethnicity and geographical location. These data may suggest the possibility to predict the discharge destination when patients are taken on to the caseload of an early intervention in psychosis (EIP) team and have important implications for psychoeducation, preparing the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…They have closed their eyes and minds to the ongoing needs of their former patients and have somehow failed to notice one of the most worrying findings ever to emerge from mental health services research. In numerous areas across the UK, the most important factor in disengagement of people with insight-impairing illnesses from psychiatric care is planned and deliberate discharge by early intervention for psychosis teams (Ahmed et al, 2019;London Early Intervention in Psychosis Clinical Reference Group, 2016;Phillipson et al, 2014;Puntis et al, 2018Puntis et al, , 2021Turner & Rainey, undated). This may also be the case in Australia, Canada and the USA and, we fear, in other countries where well-intentioned policymakers have been influenced by the early intervention movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have closed their eyes and minds to the ongoing needs of their former patients and have somehow failed to notice one of the most worrying findings ever to emerge from mental health services research. In numerous areas across the UK, the most important factor in disengagement of people with insight-impairing illnesses from psychiatric care is planned and deliberate discharge by early intervention for psychosis teams (Ahmed et al, 2019;London Early Intervention in Psychosis Clinical Reference Group, 2016;Phillipson et al, 2014;Puntis et al, 2018Puntis et al, , 2021Turner & Rainey, undated). This may also be the case in Australia, Canada and the USA and, we fear, in other countries where well-intentioned policymakers have been influenced by the early intervention movement.…”
Section: Discussionmentioning
confidence: 99%
“…There is wide variation in the proportion of those who are discharged from all psychiatric services by early intervention teams in England. This has been happening to 47% of patients in Leicester and 55% in Derbyshire (Ahmed, Peters, & Chakraborty, 2019; Phillipson, Akroyd, & Carley, 2014). A recent article reveals that fully three-quarters were discharged by an inner-city London Trust after, on average, 28 months of care (Puntis, Whiting, Pappa, & Lennox, 2021).…”
Section: Discharge From Specialist Early Intervention Servicesmentioning
confidence: 99%
“…It is the first to our knowledge to systematically apply QI methods to the challenge of care transition after FES. While there have been studies exploring referral patterns from FES in the UK (Ahmed et al, 2015;Ahmed et al, 2019), they did not directly examine patients' adherence to aftercare recommendations. This QI framework was well-suited to both implement a robust and sustainable data collection system, and support cycles of intervention to improve care transitions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some FES have clinicians accompany patients to their first session at the receiving clinic (Jones et al, 2020). As another example, in the UK, referrals from FES to primary care are quite common (Ahmed et al, 2019;Puntis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of EIP patients (83.5%) were discharged to primary care, which is substantially higher than in previous literature. 8,[15][16][17][18][19] Not only were more people being discharged to primary care, they were being discharged earlier: the median duration of EIP care was almost a year less than the 3-year stipulated treatment. This may reflect a combination of clinical judgement about need for treatment and pressure on case-load sizes.…”
Section: Discharge Pathwaysmentioning
confidence: 99%